Correlation Analysis of Land Surface Temperature (LST) and Vegetation Density Using Landsat 8 and 5 Imagery in Purwakarta Regency - Ainulmila, Aida; Tiana, S; N Mumtaz, K; S F Azhari, D; Ibrahim, F; S Anggraini, T (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Urbanization and industrial development in urban areas have led to a decrease in vegetation and an increase in land surface temperature. This phenomenon impacts microclimate change and environmental quality, as seen in Purwakarta Regency. The conversion of vegetated land into industrial and residential areas reduces the vegetation index. This vegetation index can be measured using the Normalized Difference Vegetation Index (NDVI) method. Meanwhile, monitoring the increase in surface temperature can be calculated using the Land Surface Temperature (LST) method, which can indicate physical changes on the Earth's surface. The purpose of this study is to analyze the relationship between vegetation density and the increase in surface temperature using remote sensing and Geographic Information System (GIS) methods. The analysis results show that vegetated land area decreased significantly from 67,564.8 ha (2004) to 44,970 ha (2024), while built-up land increased threefold. In the same period, the average surface temperature increased from 37.31°C to 40.41°C. The correlation analysis shows a strong positive correlation between the decrease in NDVI and the increase in LST, with a correlation coefficient of 0.707 in 2024.